Influence of site and tower types on urban natural ventilation performance in high-rise high-density urban environment. (15th July 2020) - Qin, Hao; Lin, Pingying; Lau, Stephen Siu Yu; Song, Dexuan
Abstract: This paper investigates the urban ventilation performance at the street and tower-level in the high-rise high-density urban environment of Hong Kong. By analyzing 218 residential developments and 659 residential towers from 2003 to 2013, this paper presented an innovative way of generating idealized urban forms that considers the regulatory and social-economic factors. Nine typical high-rise high-density residential urban design scenarios with different site division strategies and tower types were generated. The urban ventilation performance of these cases was studied using a validated CFD simulation technique under four different approaching wind directions. Two indices were applied to quantify the urban ventilation performance in this study, namely Wind Velocity Ratio (WVR) and Local Mean Age of Air (MAA). The results show that site and tower types have a great influence on urban ventilation. This paper concludes that extra-large sites (around 4000 square meters) have the potential of achieving the best performance in both street and urban level ventilation, while probably enduring poor indoor air quality. Therefore, a centralized tower plan without deep re-entrants is recommended for large sites. For the small (around 500 square meters) and medium (around 1000 square meters) sites that generally have poor street-level ventilation, adding service lanes can help to improve the street ventilation but may cause poor tower-level ventilation since two rows of towers are closely placed in one street block. For the small sites without service lanes, small and rectangular tower plans in one row could help to achieve better tower-level ventilation and indoor air quality potential. Highlights: View optimization principle is discovered by analyzing 218 residential development. Site division are highly related to tower types in high-rise high-density city. Extra-large site and corresponding towers have better street and urban ventilation. Small and medium site generally have poor street level ventilation. Towers with rectangular plans have good indoor natural ventilation potential.